MARKETING MIX FACTORS AFFECTING PARENTS DECIDE TO SEND THEIR CHILDREN TO INTERNATIONAL SCHOOL IN CHONBURI PROVINCE - Plangwan , Waraporn; Visitnitikitja, Chinnaso (Journal of MCU Nakhondhat, 2023)
The objective of this study aimed to 1) to study the marketing mix factors of parents’ decide to send their children to international school in Chonburi province, 2) to study the parents’ decision to send their children to study international school in Chonburi province, 3) to compare the parents' decision to send their children to study international school in Chonburi province, and 4) to study the marketing mix factors affecting parents decide to send their children to international school in Chonburi province. It is a quantitative research tool using a questionnaire. A sample of 400 people was selected using questionnaires as a study tool. Statistics used were percentage, average, T - test, F - test (One - way ANOVA), and multiple regression analysis. Findings indicated that most respondents were male, aged 41-50 years, bachelor's degree, self-employed/business owner, average monthly income of 500,001 baht or more, number of children of 1 child. The overall picture of the opinions on marketing mix factors and the parents’ decision to send their children to study international school in Chonburi province was at the highest level. Personal differences in gender, age, level of education, occupation, family wages and number of child/children did affect the parents’ decision had different effects on the parents’ decision differently. Marketing mix factors aspect such as physical appearance, products, marketing promotions, prices, personnel, operation process, and distribution channels influenced parents’ decision to send their children to study international school in Chonburi province with a statistically significant at the .05 level. Study suggestions, Process and Promotion Communication by employee’s knowledge was, Academic results are notified to parents during class. There are activities to award scholarships and various awards for students and discounts on tuition fees If many people register at the same time to build trust and confidence among customers.